Taking a Selfie: Researcher-practitioner positionality and reflexivity in project scholarship - Simon Addyman (Project Leadership and Society)
The move in project scholarship towards understanding the lived experience of projects has led to researchers engaging more deeply in project practice. Despite this, there is little evidence of how their position as researcher-practitioner influences the theorising process. This paper presents analytic autoethnography as a conceptual frame for explicating researcher-practitioner positionality as one actor. Drawing on prior data from an autoethnography, it studies an autoethnographer's reflexive engagement with participants through the interview process. It identifies four themes of reflexive engagement, leading to four dimensions of reflexivity that have a constitutive effect on positionality: The Role of the Self; Relationality - Connecting Interviews, Participants, and Diary Entries; The Role of Chance and Circumstance; Bridging Research and Practice. These four dimensions contribute to project scholarship by showing how accounting for researcher positionality in the field helps demonstrate rigour and relevance when foregrounding the lived experience of research and practice in theory development.